IMPLEMENTATION QUALITATIVE EVALUATION LOGISTICS COMPLIANCE AND ACCEPTABILITY - khusnul chotimah; Rohmat Ilzar Rozaqi; Ahmad Paisal Ariski; M Rizki Arya Effendi; M Rifky Ananda; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
The Free Nutritious Meals Programme (MBG) is a central government structural intervention to improve human resource quality ahead of the 2045 Golden Generation. Despite its scale, implementation faces operational obstacles and perception gaps at the grassroots. This study critically evaluates logistics management, regulatory compliance, and sociological barriers to MBG implementation in primary and secondary schools in Pasuruan Regency/City. Using a descriptive-evaluative qualitative method with a case study approach, data were gathered via in-depth interviews with teaching staff, direct observation of classroom distribution, and analysis of daily regulatory documents during March–April 2026. Findings revealed three main issues: (1) reduced nutritional quality caused by milk distribution cut to twice weekly, violating National Nutrition Agency Regulation No. 5 of 2026; (2) weak emergency logistics management, with rations for absent pupils ad hoc reallocated as double portions in class; and (3) low consumption due to rigid menu formulation, prompting refusals from students with allergies, boredom from monotonous menus, and vegetable aversion. Sociologically, some teaching staff expressed ideological resistance, preferring measures addressing structural poverty and education costs. Recommendations include revising local regulations to add technical guidelines for surplus management, creating a pupil allergy database, and aligning supporting local government budgets.